2005
DOI: 10.1109/tbme.2005.845243
|View full text |Cite
|
Sign up to set email alerts
|

Motion Artifact Cancellation in NIR Spectroscopy Using Wiener Filtering

Abstract: We present a Wiener filtering based algorithm for the elimination of motion artifacts present in Near Infrared (NIR) spectroscopy measurements. Until now, adaptive filtering was the only technique used in the noise cancellation in NIR studies. The results in this preliminary study revealed that the proposed method gives better estimates than the classical adaptive filtering approach without the need for additional sensor measurements. Moreover, this novel technique has the potential to filter out motion artifa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
142
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 7 publications
2
142
0
1
Order By: Relevance
“…Furthermore, unintentionally performed stimulus/task-evoked movements of the head may lead to movement artifacts. These are mostly due to changes in light coupling to the tissue, but part could also be due to genuine changes in CBF/CBV, in the fNIRI signal (Izzetoglu et al, 2005;Kurihara et al, 2003;Özgören et al, 2012;Scholkmann et al, 2010;Takahashi et al, 2012;Tax et al, 2011). That also the saliva secretion rate is accompanied with changes in extracerebral hemodynamics was initially shown by Sato et al (2011) and recently confirmed by Matsumoto et al (2012).…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…Furthermore, unintentionally performed stimulus/task-evoked movements of the head may lead to movement artifacts. These are mostly due to changes in light coupling to the tissue, but part could also be due to genuine changes in CBF/CBV, in the fNIRI signal (Izzetoglu et al, 2005;Kurihara et al, 2003;Özgören et al, 2012;Scholkmann et al, 2010;Takahashi et al, 2012;Tax et al, 2011). That also the saliva secretion rate is accompanied with changes in extracerebral hemodynamics was initially shown by Sato et al (2011) and recently confirmed by Matsumoto et al (2012).…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…There are many advanced noise reduction algorithms available that utilize different characteristics of the signal [17][18][19][20] . However if a subject or session can be excluded if data is irrecoverable (i.e.…”
Section: Processing the Fnir Data And Analysismentioning
confidence: 99%
“…In this study we have used accelerometer data as reference signal and the light intensity time-series as the primary input signal. Details of the technique can be found in [4]. To illustrate the utility of the methodology, a normalized least mean squares (NLMS) adaptive filter has been employed in this study to clean the motion artifact contaminated epochs (recorded by Channel 2).…”
Section: Resultsmentioning
confidence: 99%
“…Adaptive filters have been utilized to remove the unwanted noise [4] [8] and have been shown to produce a moderate improvement in signal to noise ratio (SNR). Izzetoglu et al also proposed Wiener [4] and discrete Kalman filtering [3] techniques for the removal of motion artifacts. Wiener filtering has been observed to produce a greater improvement in SNR than that realized using adaptive filtering methods while also reducing the need for additional sensors to capture some measure of the noise source.…”
Section: Introductionmentioning
confidence: 99%